Production and optimization of wine from banana fruits - PRADIP D. SATAV; ARCHANA S. PETHE (International Journal of Pharma and Bio Sciences, 2017)
Various physicochemical factors affect the fermentation of wine by wine yeast. Very less or no work reported the effect of different parameters on physicochemical properties of banana wine fermented using baker’s yeast (Saccharomyces cerevisiae). Thus we have investigated the suitability of banana fruit (especially ripe fruits) for wine production, and also to characterize the wine produced. In present study the effect of various parameters such as Diammonium phosphate (DAP) concentration (mg/L), pH, inoculum concentration (%) and soluble solids (OBrix) on physicochemical characteristics of banana wine was studied. The banana must was inoculated with yeast inoculum. After fermentation physicochemical parameters of the wine were analysed. With increase in DAP concentration percentage of alcohol in must was found to be increased after fermentation within a range of 4.44 to 5.90 %. With increase in initial soluble solids of must the alcohol percent of wine were also found to be increased. The alcohol % of wine fermented using different inoculum concentration was found to be increase slightly with increase in inoculum % up to 6 %. Slight decrease in alcohol % was observed with increase in pH. With increase in initial soluble solids, inoculum concentration and DAP concentration of must the alcohol percent was found to be increased. Slight decrease in alcohol % was observed with increase in pH. Various parameters affect the physicochemical property of fermented banana wine.